Co-Stimulation-Impaired Bone Marrow-Derived Dendritic Cells Prevent Dextran Sodium Sulfate-Induced Colitis in Mice - Engman, Carl; Garciafigueroa, Yesica; Phillips, Brett Eugene; Trucco, Massimo; Giannoukakis, Nick (Frontiers in Immunology, 2018)
Dendritic cells (DC) are important in the onset and severity of inflammatory bowel disease (IBD). Tolerogenic DC induce T-cells to become therapeutic Foxp3+ regulatory T-cells (Tregs). We therefore asked if experimental IBD could be prevented by administration of bone marrow-derived DC generated under conventional GM-CSF/IL-4 conditions but in the presence of a mixture of antisense DNA oligonucleotides targeting the primary transcripts of CD40, CD80, and CD86. These cell products (which we call AS-ODN BM-DC) have demonstrated tolerogenic activity in preventing type 1 diabetes and preserving beta cell mass in new-onset type 1 diabetes in the NOD mouse strain, in earlier studies. In addition to measuring efficacy in prevention of experimental IBD, we also sought to identify possible mechanism(s) of action. Weight, behaviour, stool frequency and character were observed daily for 7-10 days in experimentally-induced colitis in mice exposed to dextran sodium sulfate (DSS) following injection of the AS-ODN BM-DC. After euthanasia, the colons were processed for histology while spleen and mesenteric lymph nodes (MLN) were made into single cells to measure Foxp3+ Treg as well as IL-10+ regulatory B-cell (Breg) population frequency by flow cytometry. AS-ODN BM-DC prevented DSS-induced colitis development. Recipients of these cells exhibited significant increases in Foxp3+ Treg as well as IL-10+ Breg in MLN and spleen. Histological examination of colon sections of colitis-free mice remained largely architecturally physiologic and mostly free of leukocyte infiltration when compared to DSS-treated animals. Although DSS colitis is mainly an innate immunity-driven condition, our study adds to the growing body of evidence showing that Foxp3+ Treg and IL-10 Bregs can suppress a mainly innate-driven inflammation. The already-established safety of human DC generated from monocytic progenitors in the presence of the mixture of antisense DNA targeting the primary transcripts of CD40, CD80, and CD86 in humans offers the potential to adapt them for clinical IBD therapy.